Antigen‐driven PD‐1+TOX+BHLHE40+ and PD‐1+TOX+EOMES+ T lymphocytes regulate juvenile idiopathic arthritis in situ. Issue 4 (2nd February 2021) - Maschmeyer, Patrick; Heinz, Gitta Anne; Skopnik, Christopher Mark; Lutter, Lisanne; Mazzoni, Alessio; Heinrich, Frederik; von Stuckrad, Sae Lim; Wirth, Lorenz Elias; Tran, Cam Loan; Riedel, René; Lehmann, Katrin; Sakwa, Imme; et al.
Abstract: T lymphocytes accumulate in inflamed tissues of patients with chronic inflammatory diseases (CIDs) and express pro‐inflammatory cytokines upon re‐stimulation in vitro . Further, a significant genetic linkage to MHC genes suggests that T lymphocytes play an important role in the pathogenesis of CIDs including juvenile idiopathic arthritis (JIA). However, the functions of T lymphocytes in established disease remain elusive. Here we dissect the transcriptional and the clonal heterogeneity of synovial T lymphocytes in JIA patients by single‐cell RNA sequencing combined with T cell receptor profiling on the same cells. We identify clonally expanded subpopulations of T lymphocytes expressing genes reflecting recent activation by antigen in situ . A PD‐1 + TOX + EOMES + population of CD4 + T lymphocytes expressed immune regulatory genes and chemoattractant genes for myeloid cells. A PD‐1 + TOX + BHLHE40 + population of CD4 +, and a mirror population of CD8 + T lymphocytes expressed genes driving inflammation, and genes supporting B lymphocyte activation in situ . This analysis points out that multiple types of T lymphocytes have to be targeted for therapeutic regeneration of tolerance in arthritis. Abstract : By combined analysis of single cell transcriptomes and T‐cell receptor profiling we identified functionally distinct populations of in situ antigen‐activated T‐cells in the inflamed joints of patients with juvenile idiopathic arthritis (JIA). The results could be the basis for the development of novel biomarkers and therapeutic approaches for JIA.